Analysis of the Physical Condition Survey of Printing Athletes Silat Age 14-17 Perguruan Tunas Nusantara All of Aceh - Irfandi, Irfandi; Rahmat, Zikrur; Munzir, Munzir; Pranata, Didi Yudha; Sarwita, Tuti; Rozailini, Novia; Salbani, Salbani (Jurnal Ilmiah Teunuleh, 2023)
This research study aims to analyze the physical condition of the athletes aged 14-17 at the Tunas Nusantara College in Aceh Province. The method used is descriptive analysis of the research sample totaling 15 athletes, 9 male athletes and 6 female athletes. The instruments and data collection techniques used tests and measurements, namely in the form of a physical condition test using a 30 meter sprint, a balke test, depending on body lift (pull-up), depending on the woman's bending elbow, sit-ups and shuttle run tests. The results obtained: for the 30 meter sprit, the average classification of men was 3.87 (very good category) and women 4.59 (good category), male average classification test 56.86 (good category) female 59.14 (good category), pull up calcification male average 9 (poor category), female bending elbow 21.0 (moderate category), male average classification sit-up 44 (very good category) female 37.2 (very good category), shuttle run test average male classification 13 (good category) female 12.72 (good). The average classification of the physical condition ability of pencak silat athletes aged 14-17 years of Tunas Nusantara college in Aceh Province is in good category.